Parallel algorithms in image filtering - Čiegis, Raimondas; Jakušev, Aleksandr (Lietuvos matematikos rinkinys, 2005)
In this paper, image-filtering parallelization is described. A description of mathematical problem is given, and general parallelization tools suitable in this case are overviewed. Then the ParSol parallel array package used for parallelization is described, together with computational results of its application.